(untitled) (Bulletin of Innovative Research, 2026)
This scientific article provides a scientific, theoretical and practical justification of the possibilities of analyzing medieval written and epigraphic sources in Uzbekistan within the framework of the digital history paradigm. The relevance of the study is determined by the presence of a regulatory framework in the country regulating the protection and use of historical and cultural heritage, as well as the activation of the processes of creating digital resources by large funds and libraries. The object of the study is medieval sources (manuscripts, historical documents, catalog descriptions and their digital copies) on the territory of Uzbekistan; the subject is the methods of scientific analysis of these sources using digital history tools (metadata, digital text processing, geodata, network and corpus analysis) and their effectiveness in source studies. The methodological framework is based on an integrated approach that combines critical analysis of source studies, principles of digital archival science, metadata standardization, machine reading and indexing of texts based on OCR/HTR, as well as visual-analytical approaches (for example, restoring blurred text layers through multispectral imaging). The article shows the possibilities of reconstructing medieval sources as a “digital twin”, introducing them into scientific circulation and verifying them based on the principle of reproducible research, using the existing digital infrastructure in Uzbekistan (digital resources of the national library; electronic catalogs of manuscripts). Scientific novelty: 1) a single “digital workflow” conceptual model for analyzing medieval sources (digitization → metadata → text recognition → corpus/GIS/network analysis → verification) is proposed; 2) the joint use of HTR (manuscript text recognition) and multispectral imaging in Arabic manuscripts is scientifically substantiated by evidence that enhances source criticism.